The Influence of Pedagogical Competence, Social Competence, Personal Competence and Professional Competency on Performance Islamic Religious Education Teacher at Muhammadiyah Middle School, Banjar Regency, South Kalimantan Province - Fredy Jayen; Abdul Kadir; M. Zaid Abdurrakhman (Archives of Business Research, 2022)
This study aims to analyze the effect of pedagogic competence, social competence, personality competence and professional competence on the performance of Islamic religious education teachers in Middle Schools in Banjar Regency, South Kalimantan Province. The research method used is analytic survey. The type of research is explanatory research. The population in the study was 179 people, the determination of the number of samples used the Slovin formula with a sample of 65 people. Data collection techniques using questionnaires, documentation, interviews and observations. Validity and reliability tests were carried out on the research instrument. Data were analyzed by multiple linear regression analysis with classical assumption test. The results showed that pedagogic competence, social competence, personality competence and professional competence had a significant partial and simultaneous effect on the performance of Islamic religious education teachers in Middle Schools in Banjar Regency, South Kalimantan Province. The coefficient of determination of teacher performance can be predicted by the variables of pedagogic competence, social competence, personality competence and professional competence of 55.1%.